Implementing subtype‐specific pre‐clinical models of breast cancer to study pre‐treatment aspirin effects. (17th April 2022) - Miller, Ian S.; Khan, Sonja; Shiels, Liam P.; Das, Sudipto; O' Farrell, Alice C.; Connor, Kate; Lafferty, Adam; Moran, Bruce; Isella, Claudio; Loadman, Paul; Conroy, Emer; Cohrs, Susan; et al.
Abstract: Backgorund: Prior data suggest pre‐diagnostic aspirin use impacts breast tumour biology and patient outcome. Here, we employed faithful surgical resection models of HER2+ and triple‐negative breast cancer (TNBC), to study outcome and response mechanisms across breast cancer subtypes. Method: NOD/SCID mice were implanted with HER2+ MDA‐MB‐231/LN/2‐4/H2N, trastuzumab‐resistant HER2+ HCC1954 or a TNBC patient‐derived xenograft (PDX). A daily low‐dose aspirin regimen commenced until primary tumours reached 250 mm 3 and subsequently resected. MDA‐MB‐231/LN/2‐4/H2N mice were monitored for metastasis utilising imaging. To interrogate the survival benefit of pre‐treatment aspirin, 3 weeks post‐resection, HCC1954/TNBC animals received standard‐of‐care (SOC) chemotherapy for 6 weeks. Primary tumour response to aspirin was interrogated using immunohistochemistry. Results: Aspirin delayed time to metastasis in MDA‐MB‐231/LN/2‐4/H2N xenografts and decreased growth of HER2 + /TNBC primary tumours. Lymphangiogenic factors and lymph vessels number were decreased in HER2 + tumours. However, no survival benefit was seen in aspirin pre‐treated animals (HCC1954/TNBC) that further received adjuvant SOC, compared with animals treated with SOC alone. In an effort to study mechanisms responsible for the observed reduction in lymphangiogenesis in HER2 + BC we utilised an in vitro co‐culture system of HCC1954 tumour cells and mesenchymal stromal cells (MSC). Aspirin abrogated the secretion of VEGF‐C in MSCs and also decreased the lymph/angiogenic potential of the MSCs and HCC1954 by tubule formation assay. Furthermore, aspirin decreased the secretion of uPA in HCC1954 cells potentially diminishing its metastatic capability. Conclusion: Our data employing clinically relevant models demonstrate that aspirin alters breast tumour biology. However, aspirin may not represent a robust chemo‐preventative agent in the HER2 + or TNBC setting. Abstract : The impact of aspirin as a chemo‐preventative has been under increasing scrutiny as time has passed. Here we present a study detailing the relatively minor impact of aspirin in breast cancer prevention and survival. While Aspirin has effects on the outgrowth of lymph vessels it does not improve overall survival in clinically relevant mouse models of HER2 and triple negative breast cancer.